Building Predicates The View from Palauan - Nuger, Justin; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This volume proposes that words in Palauan are not drawn directly from a mental lexicon, but are instead composed at least partially in the syntax. Using original data from syntactic constructions not previously explored in the language, the author entertains several competing theories of word formation and highlights the compatible and incompatible aspects of each, through an exploration into new corners of Palauan syntax and morphology. The volume provides a comprehensive analysis of the syntax of Palauan that will appeal to anyone interested in Austronesian languages or formal syntactic and morphological theory more generally.
1. Setting the Stage -- 2. The Morphosyntactic Encoding of Subjects -- 3. Licensing Internal Arguments -- 4. Idioms and Lexical Insertion -- 5. From Roots to Words to Predicates -- 6. Changing Categories -- 7. Overall Conclusions -- Appendix: Remarks on the Palauan Data -- Name Index -- Palauan Predicate Index -- Subject Index. .
Keywords: Grammar, Comparative and general; Austroasiatic languages; Syntax